Marine litter plastics and microplastics and their toxic chemicals components: the need for urgent preventive measures - Frederic Gallo; Cristina Fossi; Roland Weber; David Santillo; Joao Sousa; Imogen Ingram; Angel Nadal; Dolores Romano (Environmental Sciences Europe, 2018)
Abstract Persistent plastics, with an estimated lifetime for degradation of hundreds of years in marine conditions, can break up into micro- and nanoplastics over shorter timescales, thus facilitating their uptake by marine biota throughout the food chain. These polymers may contain chemical additives and contaminants, including some known endocrine disruptors that may be harmful at extremely low concentrations for marine biota, thus posing potential risks to marine ecosystems, biodiversity and food availability. Although there is still need to carry out focused scientific research to fill the knowledge gaps about the impacts of plastic litter in the marine environment (Wagner et al. in Environ Sci Eur 26:9, 2014), the food chain and human health, existing scientific evidence and concerns are already sufficient to support actions by the scientific, industry, policy and civil society communities to curb the ongoing flow of plastics and the toxic chemicals they contain into the marine environment. Without immediate strong preventive measures, the environmental impacts and the economic costs are set only to become worse, even in the short term. Continued increases in plastic production and consumption, combined with wasteful uses, inefficient waste collection infrastructures and insufficient waste management facilities, especially in developing countries, mean that even achieving already established objectives for reductions in marine litter remains a huge challenge, and one unlikely to be met without a fundamental rethink of the ways in which we consume plastics. This document was prepared by a working group of Regional Centres of the Stockholm and Basel Conventions and related colleagues intended to be a background document for discussion in the 2017 Conference of the Parties (COP) of the Basel Convention on hazardous wastes and the Stockholm Convention on persistent organic pollutants (POPs). The COP finally approved that the issue of plastic waste could be dealt by its Regional Centres and consistently report their activities on the matter to next COP’s meetings.